'Pulling the world in and pushing it away': participating bodies and the concept of coping. Issue 2 (9th July 2019) - Duschinsky, Robbie; Reisz, Samantha; Messina, Serena
Abstract : In her lead article in this special issue, Monica Greco (2018) offers the concept of participating bodies as a 'possibility of conceiving bodies themselves—and bodily events such as disease/illness—as expressing values and perhaps even socially meaningful "preferences"'. Such a position seeks to avoid capitulation to a) an image of bodily processes as without values or responsiveness, object rather than participant; b) an image of human agents as unitary, self-knowing, sovereign choosers—unless ill. This article will explore this perspective as applied to the idea of coping. The article will explore strategies of everyday living, through particular consideration of Lauren Berlant's reading of Two Girls, Fat and Thin by Mary Gaitskill. In her interpretation of the novel, Berlant assesses the kinds of problems for subjects and bodies that may be solved or managed through participation in or refraining from participation in thinking, food or sex. The account of coping and embodiment in Berlant's reflections will then be placed in dialogue with findings by Alexandra Michel, who watched the process of physical burnout in investment banking associates during a 13-year cultural ethnography, observing as the bankers heeded or ignored the cues their bodies gave about the limits of feasible demands. The article as a whole offers an illustration of the value of Greco's reflections for offering a fresh and valuable perspective on the concept of coping.